FAKTOR-FAKTOR YANG MEMPENGARUHI KETAATAN PETUGAS KESEHATAN MELAKUKAN HAND HYGIENE DALAM MENCEGAH INFEKSI NASOKOMIAL - Serly Agustina; Murtiningsih (Jurnal Kesehatan dan Pembangunan, 2024)
Hand hygiene is the main standard in standard precautions in preventing and controlling the spread of disease in health services. There are many factors related to health workers' compliance in implementing hand hygiene. The importance of further research regarding the factors that influence health workers' compliance with hand hygiene in preventing nosocomial infections. This study aims to determine the factors that influence health workers' compliance with hand hygiene in preventing nosocomial infections. Search results from the database found 10 articles that met the research criteria. From several studies it was found that the factors that influence health workers' compliance with hand hygiene in preventing nosocomial infections are age, knowledge, motivation, availability of facilities, and supervision of the head of the room. By knowing the factors that influence compliance, it is hoped that hospital management can find solutions to increase health workers' compliance in washing hands.